The fibrous network of cellulose nanofibers can be preserved by the freeze-drying in the presence of trehalose - Popuang, Nuntanut; Ogawa, Takenobu; Kobayashi, Takashi; Matsumiya, Kentaro; Tani, Fumito (Food Science and Technology Research, 2024)
Dehydration often causes severe aggregation of biomacromolecules, leading to the loss of their physicochemical and biological properties. Given that cellulose is a useful biomass, we examined how the dehydration and rehydration processes of a cellulose nanofiber (CNF) suspension in the presence of trehalose affects the functionality of CNFs. Trehalose dihydrate was added to a CNF suspension, which was then subjected to either hot air- or freeze-drying. Upon re-hydration, the distribution of particle size, biophysical behavior, morphology, and chemical structure of the CNF fibrous network was completely reconstituted using the freeze-dried samples in the presence of 3 wt% trehalose. However, the CNF fibrous network was not fully recovered for the air-dried samples, even in the presence of a higher concentration of trehalose. The results suggest that freeze-drying in the presence of trehalose is a promising method for facilitating the dehydration and redispersal of CNFs in water to maintain a fine CNF network.